2018
DOI: 10.1038/s41598-018-26032-0
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting and normal-state anisotropy of the doped topological insulator Sr0.1Bi2Se3

Abstract: SrxBi2Se3 and the related compounds CuxBi2Se3 and NbxBi2Se3 have attracted considerable interest, as these materials may be realizations of unconventional topological superconductors. Superconductivity with Tc ~3 K in SrxBi2Se3 arises upon intercalation of Sr into the layered topological insulator Bi2Se3. Here we elucidate the anisotropy of the normal and superconducting state of Sr0.1Bi2Se3 with angular dependent magnetotransport and thermodynamic measurements. High resolution x-ray diffraction studies underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
68
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 44 publications
(60 reference statements)
12
68
3
Order By: Relevance
“…One can see that the nematicity is almost insensitive to the current flow direction. This observation is in-line with previous magnetotransport studies [5] where current flow was perpendicular to basal plane as well as with thermodynamic studies (specific heat [3] and magnetometry [9]), and it was also recently confirmed in [6]. Interestingly, in all our samples, strongest SC direction (where H c2 is maximal) either roughly coincides or is perpendicular to crystallographical axis in the basal plane, indicated by arrows in figures 1, 2, 4.…”
Section: Transport Measurementssupporting
confidence: 92%
See 4 more Smart Citations
“…One can see that the nematicity is almost insensitive to the current flow direction. This observation is in-line with previous magnetotransport studies [5] where current flow was perpendicular to basal plane as well as with thermodynamic studies (specific heat [3] and magnetometry [9]), and it was also recently confirmed in [6]. Interestingly, in all our samples, strongest SC direction (where H c2 is maximal) either roughly coincides or is perpendicular to crystallographical axis in the basal plane, indicated by arrows in figures 1, 2, 4.…”
Section: Transport Measurementssupporting
confidence: 92%
“…The most studied topological insulator material, Bi 2 Se 3 , becomes superconductive being doped with Sr, Nb or Cu, with T c around 3 K and H c2 about a few Tesla [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Nature of this superconductivity (topological or not) is in the focus of discussion during the last few years.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations